Understanding the Contextual Factors Affecting Women's Health in Sistan and Baluchestan Province in Iran: A Qualitative Study - Nasrin Rezaee; Alireza Salar; Fereshteh Ghaljaei; Naimeh Seyedfatem; Neda Rezaei (Shiraz University of Medical Sciences, 2017)
Background: Contextual factors impact health the same way social and cultural conditions do. Women's health, with its varying dimensions, is also under the influence of biological, societal, and cultural contexts. This typical condition has been developed along the continuum of their life cycle, bearing close correlation with their lif style. Therefore, identifying those marices within which women's health behaviors are formed is important.This study aims at exploring the contextual factors affecting women's health in Sistan and Baluchestan in Iran. Methods: This study was carried out using a qualitative method, on a content analysis approach. Participants were 20 middle-aged women from Zahedan who entered the study with purposive sampling method. The method of collecting data was face-to- face and through conducting semi-structured interviews. After data collection, all interviews were transcribed, andreviewed, from which categories were extracted. The semantic similarities were revised and subcategories were identified, and then the related subcategories were arranged under one category. Results: Two main categories of "features of context-based structure" and "changes in the cultural context" prove to be the basis for health behaviors in women. As for the category of "characteristics of context-based structure", individual, familial and environmental characteristics were identified, and regarding the category of "changes in the cultural context", the context-based cultural features were identified. Conclusion: The findings of the study suggest that effective contextual factors influencing women's living conditions had a decisive role in their health behaviors. In fact, the context- based structure in association with the cultural changes that have occurred in the beliefs of men and women, have had a decisive role in the women's health behaviors.